Interdisciplinary Approaches in Health Education for Sustainable Healthcare Practice - Maria Kurni Menga (Journal Interdisciplinary Health, 2025)
The sustainability of healthcare systems depends largely on the capacity of health professionals to work collaboratively across disciplines. Traditional discipline-based health education often limits coordination and integration in healthcare practice, reducing system efficiency and long-term sustainability. Interdisciplinary approaches in health education have been increasingly promoted as a strategy to prepare a collaborative workforce capable of addressing complex health challenges. This study aimed to examine the relationship between interdisciplinary approaches in health education and sustainable healthcare practice. A quantitative cross-sectional study was conducted involving 60 health professionals and health educators from multiple disciplines, including medicine, nursing, public health, pharmacy, and allied health sciences. Data were collected using a structured questionnaire measuring interdisciplinary education components and indicators of sustainable healthcare practice. Descriptive statistics and linear regression analysis were used to assess the association between interdisciplinary education and sustainable healthcare practice. The findings revealed that respondents reported moderate to high levels of interdisciplinary health education and sustainable healthcare practice. Regression analysis showed a significant positive association between interdisciplinary health education and sustainable healthcare practice (? = 0.48; p < 0.001). Higher levels of interdisciplinary learning were particularly associated with improved collaborative service delivery, preventive-oriented practice, and more efficient use of healthcare resources. Interdisciplinary approaches in health education are significantly associated with sustainable healthcare practice. Strengthening interdisciplinary learning within health education curricula may enhance collaborative competencies and support the development of more efficient, preventive, and sustainable healthcare systems. These findings highlight the importance of interdisciplinary education as a strategic foundation for advancing sustainable healthcare practice